Boosting high-performance in Zr-rich side protonic solid oxide electrolysis cells by optimizing functional interlayer - Chunmei Tang; Ning Wang; Sho Kitano; Hiroki Habazaki; Yoshitaka Aoki; Siyu Ye (Green Energy & Environment, 2025)
Protonic solid oxide electrolysis cells (P-SOECs) are a promising technology for water electrolysis to produce green hydrogen. However, there are still challenges related key materials and anode/electrolyte interface. P-SOECs with Zr-rich electrolyte, called Zr-rich side P-SOECs, possess high thermodynamically stability under high steam concentrations but the large reaction resistances and the current leakage, thus the inferior performances. In this study, an efficient functional interlayer Ba0.95La0.05Fe0.8Zn0.2O3−δ (BLFZ) in-between the anode and the electrolyte is developed. The electrochemical performances of P-SOECs are greatly enhanced because the BLFZ can greatly increase the interface contact, boost anode reaction kinetics, and increase proton injection into electrolyte. As a result, the P-SOEC yields high current density of 0.83 A cm−2 at 600 °C in 1.3 V among all the reported Zr-rich side cells. This work not only offers an efficient functional interlayer for P-SOECs but also holds the potential to achieve P-SOECs with high performances and long-term stability.